2016
DOI: 10.1177/1475725716643270
|View full text |Cite
|
Sign up to set email alerts
|

Ask Not Only ‘What Can Problem-Based Learning Do For Psychology?’ But ‘What Can Psychology Do For Problem-Based Learning?’ A Review of The Relevance of Problem-Based Learning For Psychology Teaching and Research

Abstract: Problem-based learning (PBL) is an internationally recognised pedagogical approach that is implemented within a number of disciplines. The relevance and uptake of PBL in psychology has to date, however, received very limited attention. The aim of this paper is therefore to review published accounts on how PBL is being used to deliver psychology curricula in higher education and to highlight psychological research that offers practical strategies for PBL theory and practice. The paper is divided into three sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 78 publications
2
42
0
3
Order By: Relevance
“…Video-based learning has its roots in numerous methods trying to connect psychological theory and authentic application situations systematically. Problem-based learning (e.g., Wiggins et al, 2016) or learning with the help of worked examples (Renkl, 2014) show many parallels to video-based teaching. Conceptualizing intra-and interindividual diff erences in human behaviour is one of the methodological core problems of psychological research.…”
Section: Resultsmentioning
confidence: 99%
“…Video-based learning has its roots in numerous methods trying to connect psychological theory and authentic application situations systematically. Problem-based learning (e.g., Wiggins et al, 2016) or learning with the help of worked examples (Renkl, 2014) show many parallels to video-based teaching. Conceptualizing intra-and interindividual diff erences in human behaviour is one of the methodological core problems of psychological research.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the difference in problem-based activities, class size and evaluation, research suggested that a problem-based approach can improve students' motivation and engagement (Ball & Pelco, 2006;Elder, 2015) and produced higher statistics scores (Karpiak, 2011). Although Wiggins, Chiriac, Abbad, Pauli and Worrell (2016) believed that a problem-based approach could blend theoretical and applied topics, and teach students to apply knowledge across contexts and to real world problems, some other researchers suggested that the success of this approach is dependent on the students' prior knowledge (Kirschner, Sweller, & Clark, 2006). However, all the above researchers studied how they could enhance the teaching approach for a module relevant to research methods and statistics based on collaborative problem-based learning but they did not study the influence of technology on students' views in relation to the research-teaching nexus approaches and skills development.…”
Section: Introductionmentioning
confidence: 99%
“…El aprendizaje de competencias supone el empleo de metodologías de enseñanza que permitan dicha adquisición: el trabajo en equipo, los estudios de caso o el Aprendizaje Basado en Problemas son metodologías ampliamente validadas para dicho proceso (Riesco, 2008;Robledo, Fidalgo, Arias, y Álvarez, 2015). El Aprendizaje Basado en Problemas (en adelante ABP) ha demostrado su utilidad en diferentes contextos para el aprendizaje y entrenamiento de competencias (Fernández-Martínez, García-Sánchez, DeCaso-Fuertes, Fidalgo-Redondo, y Arias-Gundín, 2006;McGrath, 2002;Steck, DiBiase, Wang, y Boukhtiarov, 2012;Wiggins, Chiriac, Abbad, Pauli, y Worrell, 2016), llegando incluso a señalarse como la más potente de las estrategias innovadoras de enseñanzaaprendizaje (Robledo et al, 2015).…”
Section: Introductionunclassified
“…Cuando se ha empleado el ABP para el entrenamiento de competencias en estudiantes universitarios, éste ha mostrado ser una metodología útil en el entrenamiento de competencias genéricas como la búsqueda, manejo e interpretación de información (Fernández y Duarte, 2013), las competencias necesarias para el éxito en los equipos de trabajo (Chay-hoon et al, 2007;Robledo et al, 2015), creatividad (Arias-Gundín, Fidalgo, y García, 2008; Zhou, 2015) o intención emprendedora (Liñán y Chen, 2009). Además, se ha empleado con éxito para el trabajo de competencias específicas tan dispares como la elaboración de informes técnicos en ingeniería (Fernández y Duarte, 2013), el desarrollo del cálculo matemático en estudiantes de secundaria (Zakariya et al, 2016) o la decisión diagnóstica en psicología (Wiggins, Chiriac, Abbad, Pauli, y Worrell, 2016). Estas mejoras competenciales se han hallado tanto en espacios presenciales de educación como en las modalidades a distancia (McGrath, 2002).…”
Section: Introductionunclassified